AMPD1 and MTHFR genes are not associated with calcium levels in rheumatoid arthritis patients with methotrexate therapy in Indonesia - Dika P. Destiani; Sumartini Dewi; Syed A. S. Sulaiman; Sofa D. Alfian; Melisa I. Barliana; Rizky Abdulah (Scientific Reports)
Abstract Rheumatoid Arthritis (RA) is a chronic and progressive autoimmune disease that affects synovial tissues has greater risk of developing secondary osteoporosis (OP). In particular, polymorphisms in Adenosine Monophosphate Deaminase 1 (AMPD1) and Methylenetetrahydrofolate Reductase (MTHFR) affect the outcome of methotrexate (MTX) treatment in patients with RA. Therefore, this study aimed to determine the association of AMPD1 rs17602729, MTHFR C677T, and MTHFR A1298C polymorphisms with MTX activity in RA patients. A retrospective design was adopted to collect data from medical records and blood samples of 99 patients experiencing outpatient care at a referral hospital in Bandung. The inclusion criteria were patients diagnosed with RA, aged 18–59 years, and receiving MTX therapy for ≥ 6 months. DNA was isolated and then amplified using Polymerase Chain Reaction (PCR), and genotyping was performed with Sanger sequencing. The kinetic photometric method was used to measure the levels of calcium in the samples. The results showed that there is no significant association between the MTHFR C677T genotype variant or allele with calcium levels, as indicated by p-values of 0.177 and 0.174, respectively. The association between the MTHFR A1298C genotype variant or alleles with calcium levels was also not significant (p = 0.206 and p = 0.090, respectively). However, most patients had normal calcium levels (76 patients; 77.6%) with the MTHFR C677T genotype variant CC and the MTHFR A1298C genotype variant AA (84 patients; 84.9%). AMPD1 rs17602729 in all patients had a CC genotype with normal calcium levels. The results suggested that there was no significant association between the genetic variation of AMPD1 rs17602729, MTHFR C677T, and MTHFR A1298C with serum calcium levels in patients with RA receiving MTX therapy.